El trabajo sexual desde una perspectiva de los derechos humanos: implicaciones del VIH/sida e infecciones de transmisión sexual. (2014)
In sex work, constant risks such as sexually transmitted infections (STIs) and human immunodeficiency virus (HIV) are assumed. This work is a profession discriminated against because of its sexual content and described from various scientific and legal discourses, which have instituted a distortion of the contingencies that are run there, legitimizing the stigmatization of those engaged in this work. Therefore, it requires comprehensive policies to prevent, treat, care for and support the problem of STIs and HIV, taking a holistic view on the prevailing human rights as a principle.